Modification of Distillation Engines Using Used Oil into Diesel and Premium Fuel Using Circular Condensation - Bambang Pratowo; Kunarto Kunarto; Widi Hantoro (Publikasi Indonesia, 2024)
In the era of the industrial revolution which is very developed today, the automotive world is also increasing, especially in vehicles that are fueled by premium diesel, due to the increasing number of vehicle demand in the wider community as more and more innovations are issued to create something latest and new, From data (Central Statistics Agency 2020) vehicles on Indonesian roads from passenger cars, goods, motorcycles, buses reached 14. Behind the positive effects due to the increasing development of the automotive world, there are also negative effects, one of which is pollution and waste generated from vehicle lubricants, oil, from periodic replacements resulting from engine maintenance that must be carried out. So the author is interested in designing a distillation machine with a condenser to convert used oil into base oil (base oil gar reduces the negative impact, the method used is by literature review, field study, preparation and testing, although the results of the test were obtained from 3 samples, namely A, B, and C with different cooking times and temperatures, it was found that the physical results obtained were too different from each other, However, not with the content in the sample, which was tested using (GC-MS) it was found that compounds with different amounts were found, namely sample A with 48 compounds, Sample B with 42 compounds and Sample C with 68 compounds, the most compounds were found in the sample with the highest cooking time and temperature with a time of 160 minutes and a temperature of 254 °C. It was found that only sample A had a premium characteristic, namely the compound octane. So that this research can be used in the community.